ЁШЛАР ЎРТАСИДА СОҒЛОМ ТУРМУШ ТАРЗИНИ ШАКЛЛАНТИРИШ ДАВЛАТ СИЁСАТИНИНГ УСТУВОР ЙЎНАЛИШИ СИФАТИДА - Саидов, А.И. (SCIENCE and SOCIETY, 2020)
The article outlines the goals and objectives of developing a healthy lifestyle psychology as a priority of public policy. The article also discusses health care psychology issues and recommendations are given.